2018
DOI: 10.1007/s00468-018-1707-y
|View full text |Cite
|
Sign up to set email alerts
|

Contact angle measurements and water drop behavior on leaf surface for several deciduous shrub and tree species from a temperate zone

Abstract: Key message Leaf CA measurement should take into account angle variation during measurement time. Leaf wettability of common deciduous forest plants is characterized by wetting contact angles ranging from 60° to 140° with a significant variation between species of the same family. Abstract Leaf wettability is an important phenomenon that has an influence on several processes such as the hydrological cycle, plant pathogen growth, or pollutant and pesticide absorption/deposition. The main objective of this resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 62 publications
0
34
0
1
Order By: Relevance
“…Likewise, denser forest stands with more canopy layers have less throughfall than sparser stands or those with fewer canopy layers. At the individual tree level, species with glabrous leaf coatings shed water more easily than those with rough surfaces, reducing leaf interception and increasing throughfall [10,11]. Other leaf characteristics, such as orientation and shape, can influence the ability of individuals to shed or intercept rainwater [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, denser forest stands with more canopy layers have less throughfall than sparser stands or those with fewer canopy layers. At the individual tree level, species with glabrous leaf coatings shed water more easily than those with rough surfaces, reducing leaf interception and increasing throughfall [10,11]. Other leaf characteristics, such as orientation and shape, can influence the ability of individuals to shed or intercept rainwater [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, leaf samples were assumed to be air-pollutant free due to the high-air quality of Virginia Tech’s campus where they were collected. However, the contact angle and its hysteresis might be affected by the level of contamination [ 30 32 ], water temperature [ 20 ], tree species [ 33 ], and the position in the crown. In future, the effects of air pollution or position in the crown might be interesting questions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the abundant wax, Papierowska et al. () found that, based on the angle of contact of water droplets, the adaxial surface of horse‐chestnut is “wettable” and the abaxial “highly wettable.” This is similar to that found in Acer pseudoplatanus and Betula pendula but in contrast to 14 of the 19 European deciduous species tested where the abaxial surface was the least wettable. Although high wettability may result in a film of water reducing gas exchange, the authors suggest that it also allows water droplets to spread out and quickly evaporate and so leaves quickly dry, reducing the time that pathogens have a moist surface to invade, and so lower the need for internal chemical defences.…”
Section: Structure and Physiologymentioning
confidence: 99%
“…Leaves have epicuticular wax containing large amounts of triterpenols and triterpenol esters including β-amyrin, a-amyrin, lupeol, friedelanol and friedelanone (Gülz, Müller, & Herrmann, 1992). Despite the abundant wax, Papierowska et al (2018) found that, based on the angle of contact of water droplets, the adaxial surface of horse-chestnut is "wettable" and the abaxial "highly wettable." This is similar to that found in Acer pseudoplatanus and Betula pendula but in contrast to 14 of the 19 European deciduous species tested where the abaxial surface was the least wettable.…”
Section: Biochemical Datamentioning
confidence: 99%